2001
DOI: 10.1300/j076v34n02_02
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Drug Treatment on Inmate Misconduct in Federal Prisons

Abstract: This paper employs a large sample to empirically evaluate the Federal Bureau of Prisons' substance abuse treatment program's effectiveness in reducing prisoner misconduct. Results show that program graduates are 74 percent less likely to engage in misconduct over a 14-month period than a comparison group. This benefit is shared by male and female inmates alike. The substantial magnitude of the effect shows that prison-based substance abuse treatment programs provide an effective management tool to correctional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
1
27
1
Order By: Relevance
“…Studies show that workplace victimization and fearfulness not only contribute to an increased risk of injury, impaired delivery of services, physical and emotional problems, and loss of privileges for inmates (Langan & Pelissier, 2001;Liebling & Maruna, 2005;Wooldredge, 1997), but also increase the physical and emotional repercussions for correctional officers (Cullen, Latessa, Burton, & Lombardo, 1993;Dennis, 1998). As a result, many correctional officers would like to resign from their correctional careers (Rugala & Isaacs, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that workplace victimization and fearfulness not only contribute to an increased risk of injury, impaired delivery of services, physical and emotional problems, and loss of privileges for inmates (Langan & Pelissier, 2001;Liebling & Maruna, 2005;Wooldredge, 1997), but also increase the physical and emotional repercussions for correctional officers (Cullen, Latessa, Burton, & Lombardo, 1993;Dennis, 1998). As a result, many correctional officers would like to resign from their correctional careers (Rugala & Isaacs, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Participation in prison-based addiction treatment appears to decrease, but not eliminate, disciplinary problems (Langan & Pelissier, 2001;Welsh, McGain, Salamatin, & Zajac, 2007). Several studies have identified risk factors for disruptive behavior in prison-based substance abuse treatment programs, including younger age, more serious prior offenses, prior misconducts, and more months in prison after treatment completion (Langan & Pelissier, 2001;Welsh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of research which suggests that the association between inmate characteristics and inmate misconduct can be mediated by program participation (French & Gendreau, 2006;Langan & Pelissier, 2002;Maguire, 1992;Prendergast, Farabee, & Cartier, 2001;Welsh, McGrain, Salamatin, & Zajac, 2008). Langan and Pelissier (2002) compared inmate misconduct among federal inmates who completed a residential drug and alcohol program to inmates who admitted to a history of substance abuse and did not participate in the program.…”
Section: Criminogenic Needs May Affect Institutional Behaviormentioning
confidence: 99%
“…Langan and Pelissier (2002) compared inmate misconduct among federal inmates who completed a residential drug and alcohol program to inmates who admitted to a history of substance abuse and did not participate in the program. Results showed that inmates who graduated from the treatment program had a significant reduction in disciplinary infractions compared to nongraduates.…”
Section: Criminogenic Needs May Affect Institutional Behaviormentioning
confidence: 99%
See 1 more Smart Citation